Men or Women: Does Gender Moderate the Effect of Overconfidence on Investment Decisions? Survey from Indonesian Retail Investors - Rahmah, Rosyidah; Nugraha, Nugraha; Kurnianingrum, Dian; Setiawan, Margareth (Future Science, 2026)
This study examines the influence of overconfidence on the investment decisions of Indonesian individual or retail investors. Furthermore, this study explores the moderating effect of gender on the relationship. The analysis uses Hayes' Moderation Model 1, utilizing a quantitative survey of 500 retail investors from the Indonesia Stock Exchange (IDX). The results showed that overconfidence significantly increased investment decisions, with the relationship being more pronounced in men than in women. Overconfidence positively influences investment decisions for both genders, with a more pronounced effect on male investors, as evidenced by the conditional effect. These findings advance behavioral finance by demonstrating gender-specific effects of overconfidence in emerging markets and suggest that investor education and risk communication strategies should be tailored to demographic characteristics.